DETERMINANT FACTORS ASSOCIATED WITH DISCIPLINE AND WORK MOTIVATION OF OFFICERS HEALTH AT PUSKESMAS PLUS PERBAUNGAN SERDANG BEDAGAI DISTRICT - Lely Masnita; Ahmad Hafizullah R; Novita Br Ginting (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
The problem with the low coverage of health services at puskesmas is partly due to the low performance of health workers who are not yet optimal. This is due to low motivation and discipline of health workers. Based on initial observations of several health workers at the Plus Perbaungan Health Center, it was found that there were problems with the discipline and work motivation of health workers. The purpose of this study was to determine the relationship between the determinant factors (goals and abilities, sanctions, achievement, recognition and responsibility) with the discipline and work motivation of health workers at the Health Center Plus Perbaungan. The research design used in this research is an analytical survey using a cross sectional study approach. The population of this study was all 78 health workers with a sample using a total sampling technique of 78 people. Data collection methods are primary data, secondary and tertiary data. The data analysis used was univariate and bivariate analysis using the chi-square statistical test. And what will happen in the study shows that there is a relationship between goals and abilities with a p value (0.000), sanctions p (0.000), firmness p (0.000) and recognition p (0.000) with discipline and work motivation, while achievement p (0.683) and responsibility p (0.577) have no relationship with discipline and work motivation. The conclusion of this study is that there is a relationship between goals and abilities, punishment, firmness and recognition with discipline and motivation, while achievement and responsibility have no relationship with discipline and work motivation in health workers.